OM MARSVINET IANDINSK FOLKLORE: Offergave, krukke, delikatesse, kæledyr, skraldebøtte, varsel og røntgen - Schjellerup, Inge (Tidsskriftet Antropologi, 1996)
Inge Schjellerup: About the Guinea-Pig in Andean Folklore. Sacrifice, jar, delikatesses, pet, dustbin, omen and x-ray The guinea pig from the Andean region in South America has a long cultural history. Archaeological evidence dates its use as domestic animal back to 5000 BC. While the guinea pig in its native environment has traditionally been raised for consumption, it also has an important social and ceremonial use in folk-medicine and in native religious practices. The author took part in a healing ceremony in central Peru where the guinea pig was used to diagnose a patient’s illness. The curanderismo is an Andean healing practise which recently has attracted the interest of western medical physicians.